Transforming Islamic Education Learning: Innovative Strategies for Generation Z Educators in Facing Generation Alpha Learners - Oseolla Savana; Ikhrom Ikhrom; Fippy Hidayati; Kurnia Nur Aliffia; Ariibah Radita Ayu Candrika; Mahfud Junaedi (Jurnal Inovasi Pendidikan dan Sains, 2025)
This article discusses the transformation of Islamic Religious Education learning by Generation Z educators in dealing with Generation Alpha students born after 2010. This research aims to identify innovative learning strategies that are relevant to the interactive, visual, and fast learning characters of Generation Alpha. The research method used is qualitative with a case study approach through interviews and observations of PAI educators from Generation Z. The results of the study show that strategies such as gamification are relevant to Generation Alpha learners. The results show that strategies such as gamification, interactive videos, and project-based learning are effective in increasing student engagement. However, challenges such as limited infrastructure, the gap between religious materials and fast learning styles, and maintaining the authenticity of Islamic values are still obstacles. In conclusion, educators need to act as innovative facilitators in creating meaningful learning experiences, and education policies need to support the development of PAI curricula that are adaptive to generational dynamics in the digital era